Planning for Change: The Forms and Flows of Lisbon Metropolitan Area Food System - Marat-Mendes, T. (54th ISOCARP Congress, 2018)
The aim of this paper is to introduce the goals and some preliminary results of a research Project ‘SPLACH – Spatial Planning for Change’, financed by European Funds through Portugal 2020 Program, which aims to contribute with new knowledge for a desirable shift of existing urban planning policies, in order to promote a low carbon and social inclusive urban system. SPLACH is about the role of cities, city networks, urban regions, metropolitan regions, and of spatial planning, in addressing structural changes (from crisis and post-crisis issues to climate change issues) and the societal challenges associated to those changes. In order to contribute to the debate placed by SPLACH, this paper focusses its analysis on the contributions of two specific working packages prepared for SPLACH Project, which deals specifically with the thematic of Urban Planning and Food, namely: i) Transition paths to urban sustainability; and ii) Food Security and Sustainability.